MTORC1-IRE1α pathway activation contributes to palmitate-elicited triglyceride secretion and cell death in hepatocytes. Issue 14 (August 2020) - Wang, Jun; Chen, Yingli; Song, Qing; Griffiths, Alexandra; Song, Zhenyuan
Lipotoxicity, defined as the cell death and/or cellular dysfunction induced by ectopic lipid deposition, plays a pathological role in the development of many metabolic diseases. Although endoplasmic reticulum stress is a well-documented mechanism behind, how endoplasmic reticulum stress is initiated during lipotoxicity remains obscure. In this study, using palmitate exposure (a 16-C saturated fatty acid) of AML12 hepatocytes, a non-transformed murine hepatocyte cell line, as an experimental model, we identified mammalian target of rapamycin complex 1 (mTORC1) to be a critical contributor to palmitate-elicited lipotoxicity, manifested by incremental triglycerides secretion and cell death. Unlike oleate (an 18-C monounsaturated fatty acid), palmitate strongly induced mTORC1 activation in hepatocytes. Importantly, mTOR inhibitors, torin-1, and rapamycin prevented hepatocytes from palmitate-induced triglyceride overproduction and cell death. We further showed that the intracellular metabolism of palmitate is required for its stimulatory effect on mTORC1. Whereas the inhibition of long-chain acyl-CoA synthetase, which converts palmitate to palmitoyl-CoA, attenuated mTORC1 activation and protected against cell death, the inhibition of stearoyl-CoA desaturase-1, the enzyme desaturating palmitate to palmitoleate, strengthened mTORC1 activation and aggravated triglyceride overproduction and cell death. Our further investigations revealed that the palmitate-induced mTORC1 activation was required for its endoplasmic reticulum stress-inducing action as mTORC1 inhibition ablated palmitate-induced activation of IRE1α, one of the three canonical pathways activated during unfolded protein response. Finally, our data demonstrated that IRE1α inhibition ameliorated triglyceride overproduction and cell death in response to palmitate exposure. Collectively, our data identify that mTORC1-IRE1α pathway is coordinately implicated in the development of lipotoxicity in hepatocyte. Impact statement: Lipotoxicity induced by saturated fatty acids (SFA) plays a pivotal role in the pathogenesis of a variety of obesity-related metabolic disorders; however, the exact mechanism(s) underlying lipotoxicity development remains elusive. The liver plays a central role in regulating intrahepatic and circulatory lipid homeostasis. In the current study, we identified that mammalian target of rapamycin complex 1 (mTORC1) activation plays an important role in regulating the detrimental effects of SFA palmitate in hepatocytes, in specific cell death, and TG overproduction. Furthermore, our data confirmed that palmitate-induced mTORC1 activation is attributable to its stimulatory effect on IRE1α, one of three canonical pathways activated during ER stress. Importantly, IRE1α inhibition prevented palmitate-triggered cell death and TG overproduction, suggesting mTORC1-IRE1α pathway is mechanistically implicated in palmitate lipotoxicity. The data obtained in the current investigation support future study to explore the therapeutic potential of targeting the mTORC1-IRE1α pathway as a novel clinical strategy for the treatment of metabolic disorders involving lipotoxicity.